Abrasives for jet cutting

The use of a stainless steel abrasive with a specific microstructure addresses the brittleness of traditional abrasives, enhancing cutting durability and reusability through impact absorption and hardness maintenance, while minimizing environmental impact.

JP7618673B2Active Publication Date: 2025-01-21VULKAN INOX
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022532041
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-04
Filing Date
2020-12-03
Publication Date
2025-01-21
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

Existing jet cutting abrasives, such as garnet and olivine sand, are brittle and have poor reusability due to high hardness, leading to rapid degradation under high impact and pressure, limiting their effectiveness in cutting processes.

Method used

A jet cutting abrasive composed of stainless steel particles with a microstructure containing martensite, austenite, chromium carbide, and/or chromium nitride, optimized to enhance temporal stability and reusability by absorbing impact loads and maintaining hardness during multiple cycles.

Benefits of technology

The stainless steel abrasive exhibits improved cutting durability and reusability, maintaining cutting quality and hardness over several cycles, reducing environmental impact by eliminating the need for rust inhibitors in the suspension.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618673000001
    Figure 0007618673000001
  • Figure 0007618673000002
    Figure 0007618673000002
  • Figure 0007618673000003
    Figure 0007618673000003
Patent Text Reader

Abstract

The present invention proposes an abrasive for jet cutting containing particles made of stainless steel. [Solution] The stainless steel has a microstructure that, based on the microstructure, contains martensite, particularly in the range of 20 to 100 weight %, austenite in the range of 0 to 50 weight %, and chromium carbide, chromium nitride, and / or mixtures thereof in the range of 0 to 45 weight % combined, with the proportions selected based on the microstructure so that the total amount does not exceed 100 weight %. The jet cutting abrasive has particularly excellent life and reusability. The present invention also proposes a jet cutting suspension containing at least the proposed jet cutting abrasive and a suspension medium, and the use of the jet cutting abrasive for cutting a workpiece.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an abrasive for jet cutting, to a suspension for jet cutting and to the use of the abrasive for jet cutting. [Background technology]

[0002] Jet cutting is known per se and is used to cut or cut various materials. Jet cutting is not assigned to any manufacturing process standard, but is often classified in DIN 8200 under the broad concept of blasting or blast chipping due to the principle of removal. However, depending on the pressure, it is necessary to distinguish between the various blasting systems, which cannot be compared with classical blasting processes for surface treatment. The essential difference lies in the speed of the abrasive directed at the surface. In classical surface treatment, this speed is at most 160 m / s, in comparison with jet cutting, abrasive velocities of 500 m / s and even more are achieved in jet cutting. In addition, there is an essential difference in the impact angle of the abrasive with the surface of the blasting material. In classical blasting processes for surface treatment, a flat angle or an angle of less than 90° is sought in order to minimize the recoil effects of microchipping of the surface and to achieve wear of the surface by microchipping. In comparison with abrasive blasting, the abrasive is directed at the surface at an angle of 90°, causing impact or recoil wear, which leads to erosive removal. Abrasives for material separation must withstand significantly higher requirements than those required for classical blasting processes for surface preparation. These are especially due to the high impact velocity and associated impact pressure. Furthermore, the abrasive must directly erode the material surface and show little recoil effect. In comparison with other cutting methods such as laser beam cutting or plasma cutting, jet cutting is a non-thermal cutting process. In addition to dry jet cutting, water jet cutting is particularly popular, in which water is supplied to the material under high pressure from a nozzle and erodes the material. In order to improve the cutting performance and the quality of the cut, abrasives can be added in the cutting processes of dry jet cutting and water jet cutting. The abrasives can be various materials, preferably of high hardness.

[0003] Garnet, olivine sand or corundum are usually added in the process as the main abrasives used. The advantage of these garnet, olivine sand or corundum is that they inherently have a high hardness of 6.5-9Mos, which corresponds to about 1120-2060HV (Vickers hardness). Moreover, these minerals, among others, fall into the category of cubic lattice type with hexagonal octahedral structure. This makes these minerals applicable in material removal and cutting processes with sharp chip / edge shapes and excellent performance.

[0004] However, due to their high hardness, these materials are very brittle and susceptible to shock and pressure loads, so that garnets, for example, break very quickly during use and can only be reused with great effort or suffer high losses due to breakage. Garnets are typically reusable for 2 to a maximum of 3 cycles. Summary of the Invention [Problem to be solved by the invention]

[0005] Thus, the abrasive may still show potential for improvement, especially in terms of its time stability and reusability.

[0006] It is therefore an object of the present invention to provide an improved abrasive for jet cutting. [Means for solving the problem]

[0007] This problem is solved by an abrasive for jet cutting according to claim 1, as well as a suspension for jet cutting according to claim 10 and the use of the abrasive for jet cutting according to claim 11. Preferred embodiments of the invention are set out in the dependent claims, the description, the examples or the figures, and further features explained or shown in the dependent claims or in the description, examples or figures may, individually or in any combination, be taken as the subject of the invention, unless the context clearly indicates otherwise.

[0008] According to the present invention, there is proposed an abrasive for jet cutting, comprising particles of stainless steel, the stainless steel comprising a microstructure, the microstructure being based on the microstructure and having at least - in particular, martensite in the range of 20% by weight to 100% by weight, - austenite in the range of 0 weight % or more and 50 weight % or less; - chromium carbide, chromium nitride and / or mixtures thereof in a range of from 0 to 45% by weight, and the proportions are selected based on the microstructure to total less than or equal to 100% by weight.

[0009] For the purposes of the present invention, an "abrasive" should be understood to be an auxiliary substance that can be added to a jet cutting agent to improve the cutting performance of the jet cutting agent.

[0010] For purposes of the present invention, this shall be understood to include "steel" and to be a material consisting primarily of iron.

[0011] For the purposes of the present invention, the term "stainless" refers to the property of being substantially inert with respect to reactions with the environment and / or the natural atmosphere. In particular, stainless steel should be understood to mean a steel that does not substantially react with the surrounding air and / or air humidity under normal conditions.

[0012] For the purposes of the present invention, "structure" is to be understood as the microstructure of the steel, i.e. in particular that the composition of the steel consists of a plurality of sub-volumes, each of which is homogeneous in first approximation with respect to a fixed coordinate system located within the material, in terms of its composition and the spatial arrangement of its blocks.

[0013] For the purposes of the present invention, "martensite" is to be understood to mean a steel having a martensitic structure, which for the purposes of the present invention is understood as a metastable structure of the steel in a tetragonally distorted body-centered lattice, which arises during the manufacture of the steel during cooling, in particular by falling below the start temperature of martensite and being transformed from the austenitic structure.

[0014] For the purposes of the present invention, "austenite" is to be understood as meaning a steel with an austenitic structure, which for the purposes of the present invention is to be understood as meaning the metastable structure of the steel at room temperature, which has a face-centered cubic lattice, which occurs during the manufacture of the steel, in particular at high temperatures, and which remains incompletely transformed into martensite upon cooling / quenching. For the purposes of the present invention, austenite is therefore to be understood in particular as retained austenite.

[0015] For purposes of the present invention, "chromium carbide" should be understood to mean a precipitate in stainless steel consisting essentially of chromium and carbon. For purposes of the present invention, "chromium nitride" should be understood to mean a precipitate in stainless steel consisting essentially of chromium and nitrogen. For purposes of the present invention, mixtures of "chromium carbide" and "chromium nitride" are also mixtures of chromium carbide and chromium nitride precipitates, and mixtures of chromium carbide and chromium nitride precipitates.

[0016] Advantageously, the jet cutting abrasives described above can improve time stability and reusability compared to known abrasives, which can in particular protect the environment. Furthermore, the jet cutting abrasives can achieve good cutting at good cutting speeds during jet cutting. Although the abrasives are metallic, they can be made rust-free.

[0017] Without being bound by theory, the martensitic microstructural components contribute in part to achieving a high base hardness of about 800 HV and a certain brittleness, which results in a garnet-like sharp structure when the grains break down, resulting in good cutting durability and good material removal. Austenite, chromium carbides and chromium nitrides can then selectively further improve the properties of the martensite.

[0018] Furthermore, without being bound by theory, austenite is favorable to pressure in machining processes because this microstructure in conjunction with other microstructural components can achieve more advantages than garnet. Austenite is in a metastable state and first hardens in the case of pressure, such as that generated by high pressure or deformation during machining processes, and can be transformed into deformation-induced martensite above a certain hardening limit. The austenite structure is very deformable due to its face-centered cubic lattice, which gives it excellent toughness and allows it to receive and absorb shock loads very well. As a result, when the abrasive according to the invention has austenite and is under pressure, the abrasive can better absorb high impact / shock and pressure loads due to the retained austenite present. The material is therefore not necessarily brittle and fractured, but continues to harden until the retained austenite is transformed into martensite and becomes brittle. However, this is advantageously only the case after several reuse cycles. Advantageously, the selectively preferably present austenite allows the abrasive to harden slightly and steadily under pressure during jet cutting, so that the cutting durability remains stable over several cycles without compromising the quality of the cut.

[0019] Furthermore, without being bound by theory, the selective presence of chromium carbide and / or chromium nitride further improves the life, cutting durability and reusability of the abrasive. In particular, further improved wear resistance can be achieved by these microstructural components. Furthermore, the hardness of the abrasive can be further improved by the chromium carbide and / or chromium nitride.

[0020] The absence of rusting of the abrasives has the advantage that when they are used in jet cutting suspensions, no rust inhibitors need to be added to the suspension, which is particularly environmentally friendly and simplifies the treatment of the resulting suspensions.

[0021] The above microstructural composition can be advantageously influenced by the chemical composition of the stainless steel and, optionally, by heat treatment of the stainless steel.

[0022] In one embodiment, martensite may at least partially comprise an intermediate structure, whereby martensite should also be understood as a mixture of martensite and an intermediate structure, whereby for the purposes of the present invention "intermediate structure" should be understood to mean the structure, also known as bainite, which may arise on cooling of austenite.

[0023] Preferably, the proportions of the above structures are selected so that together they add up to 100% by weight, based on the microstructure.

[0024] The abrasive may preferably comprise other abrasives than the stainless steel particles, such as metal abrasives or mineral abrasives, whereby adjustment of the cutting and / or wear properties can be advantageously achieved.

[0025] Preferably, the jet cutting abrasive contains 95% to 100% by weight, particularly preferably 98% to 100% by weight, of stainless steel particles based on the total weight of the jet cutting abrasive, which advantageously allows the abrasive to have particularly uniform cutting and / or wear properties.

[0026] Preferably, the microstructure may comprise chromium carbide, chromium nitride and / or mixtures thereof in a combined amount in the range of 3% to 35% by weight, preferably 10% to 30% by weight, especially 24% to 28% by weight, based on the microstructure.

[0027] This can advantageously achieve that the abrasive has further improved wear resistance or cutting durability.Furthermore, this can advantageously achieve that the abrasive has a particularly high hardness.In particular, chromium carbide, chromium nitride and / or mixtures thereof in the above ranges can simultaneously achieve sufficiently high hardness and sufficiently good wear properties or cutting durability.

[0028] In a preferred embodiment, the microstructure may comprise chromium carbide in the range of 3% to 35% by weight, preferably 10% to 30% by weight, in particular 24% to 28% by weight, based on the microstructure. In an alternative preferred embodiment, the microstructure may comprise chromium nitride in the range of 3% to 35% by weight, preferably 10% to 30% by weight, in particular 24% to 28% by weight, based on the microstructure.

[0029] Suitably, the microstructure may contain in the range of 5% to 47% by weight austenite, preferably 15% to 40% by weight, especially 25% to 35% by weight, based on the microstructure.

[0030] It can thereby be advantageously achieved that the abrasive has particularly good wear properties, in particular that it has sufficient crash or impact strength so that it does not shatter too quickly, and at the same time, due to the above-mentioned proportion of austenite, it can be achieved that the hardness of the abrasive is not excessively impaired.

[0031] In a preferred embodiment, the microstructure may contain martensite in the range of 15% to 75% by weight, preferably 18% to 72% by weight, based on the microstructure.

[0032] Preferably, the microstructure is based on the microstructure: - Martensite in the range of 18% by weight to 72% by weight, -Austenite in the range of 5% by weight to 47% by weight - chromium carbide, chromium nitride and / or mixtures thereof in the range of 3% to 35% by weight in total, The proportions are selected so that they add up to 100% by weight based on the microstructure.

[0033] Preferably, the stainless steel is based on the alloy: - chromium in the range of 10% to 35% by weight, - molybdenum in the range of 0 to 3% by weight, - nickel in the range of 0% to 1% by weight, - Carbon in the range of 0% to 2.5% by weight, Nitrogen in the range of 0% to 2.5% by weight, - Trace elements in the range of 0% to 1% by weight and -Residual iron and the alloy may comprise an alloy including carbon and nitrogen in a range of 0.2% to 2.5% combined by weight based on the alloy.

[0034] It can thereby be advantageously achieved that the structural composition according to the invention can be set particularly simply. For example, it is realized that the structural composition according to the invention can already be achieved after cooling of the cast steel with the above-mentioned elemental composition. Furthermore, it can be advantageously achieved that the structural composition can be set even more advantageously within the required range by a subsequent heat treatment. In particular, it can be achieved that a steel with the above-mentioned composition is provided by casting and that immediately after cooling and / or after heat treatment it has the structural composition according to the invention. Thus, a particularly good manufacturability of the abrasive can be advantageously achieved by the above-mentioned steel composition.

[0035] It is understood that common impurities are included in the composition. Preferably, the alloy may consist of the above components.

[0036] Preferably, the alloy contains carbon and nitrogen in a range of from 0.6 to 2.5% by weight, preferably from 0.8 to 2.3% by weight, particularly preferably from 1.2 to 2.1% by weight, and in particular from 1.8 to 2% by weight, based on the alloy.

[0037] It is thereby easily achieved to keep the ratio of chromium carbide, chromium nitride and mixtures thereof within the advantageous range, so that it is advantageously achieved that the abrasive has a particularly good wear resistance or cutting durability, while at the same time a high hardness.

[0038] Preferably, the alloy contains chromium in the range of 15% to 33% by weight, preferably 20% to 31% by weight, in particular 25% to 30% by weight, based on the alloy.

[0039] It can be achieved that the steel does not rust sufficiently due to the above-mentioned chromium content. Furthermore, it can be achieved that the ratio of chromium carbide, chromium nitride and mixtures thereof can be easily kept in the advantageous range. It can therefore be advantageously achieved that the abrasive has particularly good wear resistance or cutting durability and at the same time a high hardness. For the purposes of the present invention, it is self-evident that the stainless steel can have chromium, carbon and / or nitrogen without necessarily having chromium carbide and / or chromium nitride.

[0040] Preferably, the stainless steel is based on the alloy: - chromium in the range of 10% to 35% by weight, - Carbon in the range of 0% to 2.5% by weight, Nitrogen in the range of 0% to 2.5% by weight, - Trace elements in the range of 0% to 1% by weight and -Residual iron and the alloy may comprise an alloy including:

[0041] Preferably, the stainless steel is based on the alloy: - chromium in the range of 10% to 35% by weight, - Carbon in the range of 0% to 2.5% by weight, Nitrogen in the range of 0% to 2.5% by weight, and -Residual iron and the alloy may comprise an alloy including carbon and nitrogen in a total amount of 0.2% to 2.5% by weight based on the alloy.

[0042] Preferably, the stainless steel is based on the alloy: - chromium in the range of 10% to 35% by weight, - Carbon in the range of 0.2% by weight to 2.5% by weight, - Trace elements in the range of 0% to 1% by weight and -Residual iron The alloy may be made of an alloy including

[0043] Preferably, the stainless steel is based on the alloy: - chromium in the range of 10% to 35% by weight, - Carbon in the range of 0.2% to 2.5% by weight -Residual iron The alloy may be made of an alloy including

[0044] In an alternative preferred embodiment, the stainless steel is based on an alloy: - chromium in the range of 10% to 35% by weight, - 0.5% to 1.5% by weight of molybdenum, - Carbon in the range of 1.1% to 2.4% by weight, - Nitrogen in the range of 0.1% to 0.4% by weight -Residual iron and the alloy contains carbon and nitrogen in a range of 1.5% to 2.5% by weight based on the alloy.

[0045] Preferably, the stainless steel is based on the alloy: - chromium in the range of 10% to 35% by weight, - 0.5% to 1.5% by weight of molybdenum, - Carbon in the range of 1.5% to 2.0% by weight, -Nitrogen in the range of 0.2% to 0.3% by weight -Residual iron and The alloy contains carbon and nitrogen in a range of 1.8% to 2.2% combined by weight, based on the alloy.

[0046] In an alternative preferred embodiment, the stainless steel is based on an alloy: - chromium in the range of 10% to 35% by weight, - Carbon in the range of 1.1% to 2.4% by weight, - Nitrogen in the range of 0.1% to 0.4% by weight -Residual iron and the alloy contains carbon and nitrogen in a range of 1.5% to 2.5% by weight based on the alloy.

[0047] Preferably, the stainless steel is based on the alloy: - chromium in the range of 10% to 35% by weight, - Carbon in the range of 1.5% to 2.0% by weight, -Nitrogen in the range of 0.2% to 0.3% by weight -Residual iron and the alloy contains carbon and nitrogen in a range of 1.8% to 2.2% by weight based on the alloy.

[0048] In an alternative preferred embodiment, the stainless steel is based on an alloy: - chromium in the range of 10% to 35% by weight, - 0.5% to 1.5% by weight of molybdenum, - Carbon in the range of 1.0% to 2.5% by weight -Residual iron The alloy may be made of an alloy including

[0049] Preferably, the stainless steel is based on the alloy: - chromium in the range of 10% to 35% by weight, - 0.5% to 1.5% by weight of molybdenum, - Carbon in the range of 1.7% by weight to 2.2% by weight -Residual iron The alloy may be made of an alloy including

[0050] Preferably, the stainless steel particles may comprise an equivalent diameter D90 in the range of 0.01 mm to 1 mm, preferably 0.05 mm to 0.4 mm, in particular 0.09 mm to 0.315 mm, alternatively preferably 0.01 mm to 0.5 mm, in particular 0.01 mm to 0.2 mm.

[0051] For the purposes of the present invention, "equivalent diameter" is understood to mean that spheres having the same diameter have the same diameter-specific properties. In particular, equivalent diameter is understood to mean the equivalent diameter determined by sieving according to DIN 66165-2:2016-08. For the purposes of the present invention, "equivalent diameter D90" is understood to mean that 90% by weight of the sample has an equivalent diameter smaller than or equal to "equivalent diameter D90".

[0052] With particles within the above range of equivalent diameter, it is advantageously possible to achieve good suspension of the abrasive, which can be used in particularly fine cutting jets, and furthermore, with such particles, particularly good life and cutting performance can be achieved.

[0053] Preferably, the stainless steel particles have a hardness in the range of 600 HV0.2 to 1000 HV0.2, preferably 7000 HV0.2 to 900 HV0.2, in particular 780 HV0.2 to 830 HV0.2, in particular as measured according to DIN EN ISO 6507-1:2018-07.

[0054] Compared to known and used abrasives, the proposed abrasive is characterized by a tough base matrix with hard carbides. The excellent toughness properties allow it to withstand high impact or pressure loads, which occur in particular when the abrasive is struck by a high-pressure water jet and when the abrasive strikes a material surface. Due to the above-mentioned hardness as well as the carbides present, it can be achieved that the abrasive produces particularly good cutting performances. At the same time, due to the microstructural composition, it can be achieved that the abrasive is decomposed favorably only after a few cycles of use, compared to abrasives with similar hardness. This can advantageously achieve particularly good reusability of the abrasive.

[0055] Preferably, the abrasive has a bulk density in the range of 3.5 g / cm3 to 5 g / cm3, preferably 3.6 g / cm3 to 4.0 g / cm3, in particular the bulk density being measured according to DIN ISO 697:1984-01.

[0056] Preferably, the particles may be selected from shot, cut wire, grit, and mixtures thereof, with the particles preferably being grit.

[0057] For purposes of the present invention, "shot" shall be understood to mean substantially spherical particles. For purposes of the present invention, "cut wire" shall be understood to mean substantially cylindrical particles. Furthermore, grit shall be understood to be substantially angular irregular particles.

[0058] Particularly good cutting performances can be achieved with the above particles. It has been found that particularly good cutting performances with abrasives can be achieved with grit.

[0059] The invention further provides a jet cutting suspension, which comprises at least one jet cutting abrasive as defined above and a suspension medium, preferably water.

[0060] Preferably, the suspension comprises a suspending medium, particularly water, and an abrasive, the weight ratio of the suspending medium to the abrasive being in the range of from 9:1 to 23:1, preferably from 11:1 to 19:1, more preferably from 12 to 16:1, and particularly preferably from 13.5:1 to less than 14.5:1.

[0061] This has the advantage that the cutting speed during jet cutting with the suspension can be set particularly well and high cutting performance can be achieved.

[0062] Preferably, the suspension does not contain a rust inhibitor.

[0063] This may advantageously be achieved allowing environmentally friendly processing of the suspension.

[0064] It is preferred that the suspension comprises an additive, preferably an additive for stabilizing the suspension, which preferably comprises a polymer, preferably a homopolymer, particularly preferably starch.

[0065] In a preferred embodiment, the suspension has water as the suspension medium and starch as the additive, preferably in a weight ratio of water to starch in the range of 120:2 to 120:0.5, for example 120:1.

[0066] Furthermore, the present invention proposes the use of the above-mentioned abrasive for jet cutting for cutting a workpiece, which means that the above-mentioned abrasive is used in jet cutting by feeding it at high speed to the workpiece to be cut, thereby cutting the workpiece by microchipping.

[0067] Preferably, the abrasive may be used in said suspension at a working pressure ranging from ≧1000 bar to ≦6000 bar, preferably from ≧3000 bar to ≦6000 bar.

[0068] Particularly good cutting performances can be achieved at the above mentioned working pressures. Surprisingly, it has been shown that the abrasives when used in these working pressure ranges have a particularly high reusability, in spite of their high hardness, compared to known abrasives for jet cutting.

[0069] Preferably, the abrasive is used at a speed that strikes the workpiece in the range of 500 m / sec to 600 m / sec, preferably 550 m / sec to 650 m / sec. Effect of the Invention

[0070] Surprisingly, it has been shown that the above abrasives achieve good cutting performance when impacting the workpiece at the above mentioned velocities, while at the same time providing good reusability, in particular that the abrasives can withstand high impact or pressure loads when impacted at the above mentioned velocities, without loss of cutting quality, and that their properties, especially particle size, remain stable over several cycles. [Brief description of the drawings]

[0071] [Figure 1] 1 shows the sieve distribution in weight percent versus cycle number for a life test of an abrasive according to Example 2 in the range of 0 to 20 cycles. [Diagram 2] 1 shows the sieve distribution in weight percent versus number of cycles in a life test of an abrasive according to a comparative example. [Diagram 3]1 shows the sieve distribution in weight percent versus cycle number for a life test of an abrasive according to Example 2 ranging from 0 to 40 cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0072] Further advantages and advantageous embodiments of the jet cutting abrasive according to the invention are shown by examples and figures and are explained in the following description. It should be noted that the examples and figures are merely of an illustrative nature and are not intended to limit the invention in any way.

[0073] Example 1 A jet cutting abrasive was provided. It had stainless steel particles. The stainless steel was composed of a microstructure including 72 wt% martensite, 25 wt% austenite, and 3 wt% chromium carbide. The stainless steel was composed of an alloy including 0.8 wt% carbon, 15 wt% chromium, and residual iron. It had a hardness in the range of 600-740 HV. The abrasive had good cutting properties and good toughness. Compared to garnet, the abrasive of Example 1 also had good wear properties or good cutting durability. Without being bound by theory, good cutting properties could be achieved due to the high martensite content, but the wear properties were poor compared to abrasives with a high chromium carbide content.

[0074] Example 2 A jet cutting abrasive was provided. It had stainless steel particles. The stainless steel was composed of a microstructure including 44% by weight martensite, 30% by weight austenite, and 26% by weight chromium carbide. The stainless steel was composed of an alloy including 2% by weight carbon, 30% by weight chromium, and residual iron. It had a hardness of about 800 HV. The abrasive had good cutting properties and good toughness. Compared to garnet and the other examples, the abrasive of Example 2 had the best wear properties while exhibiting very good cutting properties.

[0075] Example 3 A jet cutting abrasive was provided. It had stainless steel particles. The stainless steel was composed of a microstructure containing 18% by weight martensite, 47% by weight austenite, and 35% by weight chromium carbide. The stainless steel was composed of an alloy containing 2.5% by weight carbon, 35% by weight chromium, and residual iron. It had a hardness of 800-850 HV. The abrasive still had good cutting properties and good toughness. Compared to garnet, the abrasive of Example 3 also had good wear properties or good cutting durability. Without being bound by theory, good toughness could be expected from the relatively high proportion of austenite, but it cannot compensate for the low toughness due to the high proportion of chromium carbide, so overall a lower performance was achieved than the abrasive of Example 2.

[0076] (Comparative Example) Garnet was used as the comparative abrasive.

[0077] (Life test) Jet cutting tests were carried out using the abrasives of Example 2 and Comparative Example to compare their properties. A suspension consisting of the abrasive, water and starch was prepared and sprayed onto a V2A steel plate with a thickness of 20 mm. The jet was carried out at a cutting speed of 25 mm / min, a specimen thickness of 20 mm, a cutting width of 1.0 mm, fresh particles of 300 g / min, a cutting length of 400 mm, a nozzle to specimen surface distance of 7 mm, and a pressure of 3200 bar and a flow rate of 3053 L / min for good cutting quality. The abrasives were collected and sieved on a fractional sieve after each cycle to obtain a sieve distribution reflecting the distribution of equivalent diameters. The abrasives were then returned to the jet cutting machine and used for the next cycle.

[0078] The results of the life tests are shown in the figures and are discussed in detail below.

[0079] Figures 1 to 3 show the results of the life test for Example 2 and Comparative Example. For Example 2, the corresponding weight ratios in % of the sieving fraction are shown as histograms for each of the 5 cycles. For Comparative Example, the corresponding weight ratios are shown as % of the sieving fraction for the first 3 cycles. The mesh widths of the sieves used for fractionation in the case of sieving are shown in mm. Furthermore, for the most pronounced fractions, a logarithmic curve is fitted to the measured data and shown as a dashed line.

[0080] Example 2 and the comparative example had the sieve fraction with a mesh width of 0.21 mm as the largest fraction exceeding 60% by weight as new particles.

[0081] From FIG. 1, it can be seen that the fraction consisting of 0.21 mm mesh width of the abrasive of Example 2 is hardly decreased, and even after 20 cycles, still accounts for about 55% by weight of the sieve fraction.

[0082] A comparable life test of the garnet according to the comparative example shown in Figure 2 showed that already after one cycle the fraction consisting of a mesh width of 0.21 mm was below 35% by weight. After three cycles this fraction was only just over 10% by weight, so that already after three cycles this abrasive was no longer usable.

[0083] 3 shows the life test of the abrasive of Example 2. It can be seen that even after 40 cycles, the fraction consisting of 0.21 mm mesh width still accounts for the largest proportion, indicating that the abrasive can still be used accordingly.

[0084] As a result, the polishing agent according to the invention exhibits significantly improved time stability and reusability compared to known polishing agents.

Claims

1. 1. An abrasive for jet cutting comprising particles of stainless steel, the stainless steel comprising a microstructure, the microstructure comprising at least Martensite in the range of -15% by weight or more and less than 100% by weight; Austenite in the range of -5% by weight to 47% by weight, - chromium carbide, chromium nitride and / or mixtures thereof in a combined range of from 3% to 35% by weight, and a ratio of the stainless steel selected based on the microstructure such that the martensite, the austenite, and the chromium carbide, the chromium nitride, and / or the mixture thereof are 100% by weight or less in total, and the stainless steel is produced from an alloy, and the alloy is selected based on the alloy, Chromium in the range of 10% by weight to 35% by weight, - Molybdenum in the range of 0% by weight to 3% by weight, - Nickel in the range of 0% to 1% by weight, - Carbon in the range of 0% to 2.5% by weight, Nitrogen in the range of 0% to 2.5% by weight, - Trace elements in the range of 0% by weight to 1% by weight, and - Residual iron wherein the alloy contains the carbon and the nitrogen in a total amount in the range of 0.8% by weight or more and 2.5% by weight or less based on the alloy.

2. 2. The abrasive for jet cutting according to claim 1, wherein the microstructure contains chromium carbide, chromium nitride, and / or a mixture thereof in a range of 10% by weight or more and 30% by weight or less based on the microstructure.

3. 3. The abrasive for jet cutting according to claim 1, wherein the microstructure contains austenite in a range of 15% by weight to 40% by weight based on the microstructure.

4. 4. The abrasive for jet cutting according to claim 1, wherein the alloy contains carbon and nitrogen in a range of 1.2% by weight or more and 2.1% by weight or less based on the alloy.

5. 5. The abrasive for jet cutting according to claim 1, wherein the alloy contains chromium in a range of 15% by weight to 33% by weight based on the alloy.

6. 6. The abrasive for jet cutting according to claim 1, wherein the stainless steel particles have an equivalent diameter D90 in the range of 0.01 mm or more and 1 mm or less.

7. 7. The abrasive for jet cutting according to claim 1, wherein the stainless steel particles have a hardness in the range of 600 HV0.2 or more and 1000 HV0.2 or less.

8. 8. The abrasive for jet cutting according to claim 1, wherein the particles are selected from the group consisting of shot, cut wire, grit, and mixtures thereof.

9. A jet cutting suspension comprising at least one jet cutting abrasive according to any one of claims 1 to 8 and a suspension medium.

10. Use of the abrasive for jet cutting according to any one of claims 1 to 8 for cutting a workpiece.

Citation Information

Patent Citations

  • Highly corrosion-resistant fuel injection device

    JP1994058218A

  • Corrosion resistant steel for induction hardening

    JP2000328204A

  • Martensitic stainless steel grain

    JP2002317203A

  • Water-jet peening method and apparatus

    JP2011056616A

  • Method and blasting means for producing a satin finish on an aluminum substrate

    JP2015532893A